A brief review to improve the efficiency of solar still using efficient phase change materials. (2022) - Thakur, Vinay; Kumar, Nitin; Kumar, Sushil; Kumar, Naresh
Abstract: To preserve the purity of water, solar desalination process is used in solar stills for which the analysis work is employed to understand the factors that affect the conditions of such process at different stages. Many investigators have tried to improve the efficiency and productivity of solar still using different techniques. In this article the use of most efficient materials and the experimental work in the field of solar still is concisely reviewed. In a technique, Paraffin wax gives the maximum output when used with different Phase Change Materials (PCMs) as productivity and thermal conductivity increases. In a modified still, when wicks were used; the distillate output obtained and gain in overall productivity was increased. Further, when Graphene oxide nanoparticles were used, the daily basis efficiency and thermal conductivity was improved. Thermal efficiency was raised and in addition there was improvement in fresh-water yield when collective PCMs, reflectors and nano-coating paint mixed with nanoparticles were used. These were highly efficient PCMs used in the solar still and it has been concluded that paraffin wax gives the maximum output and productivity as compared to other phase change materials.